1965
DOI: 10.1080/00401706.1965.10490300
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood Estimation in the Weibull Distribution Based On Complete and On Censored Samples

Abstract: This paper is concerned with the two-parameter Weibull distribution which is widely employed as a model in life testing. Maximum likelihood equations are derived for estimating the distribution parameters from (i) complete samples, (ii) singly censored samples and (iii) progressively (multiple) censored samples. Asymptotic variance-covariance matrices are given for each of these sample types. An illustrative example is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(117 citation statements)
references
References 12 publications
0
111
0
6
Order By: Relevance
“…-the maximum likelihood estimation (MLE), which maximizes the log likelihood function (Cohen, 1965);…”
Section: Weibull Distributionmentioning
confidence: 99%
“…-the maximum likelihood estimation (MLE), which maximizes the log likelihood function (Cohen, 1965);…”
Section: Weibull Distributionmentioning
confidence: 99%
“…Cohen [5] concluded that the approximate variance covariance matrix may be obtained by replacing expected values by their MLE's. To obtain elements for information matrix, let …”
Section: Approximate Inferencementioning
confidence: 99%
“…The asymptotic variance-covariance matrix for 1 2 1 ,,    and 2  can be obtained by inverting the information matrix with the elements that are negative of the expected values of the second order derivatives of logarithms of the likelihood functions. Cohen (1965) concluded that the approximate variance covariance matrix may be obtained by replacing expected values by their MLEs. Now the approximate sample information matrix will be …”
Section: Maximum Likelihood Estimationmentioning
confidence: 99%
“…As the integral in the right side of (9) has no analytical solution, we have to use a numerical technique to solve the integral. According to the invariance property of the MLE, the MLE of the relative risk rates 1  , can be obtained by replacing the MLE of 1 2 1 ,,    and 2  in (9). Based on the above results, When 12 1   , the MLE's of 1  and 2  and the relative risk rates 1  and 2  , corresponds to the results of the exponential distribution obtained by Hemmati and Khorram [11], when the cause of failure is known.…”
Section: Maximum Likelihood Estimationmentioning
confidence: 99%